Relative peripheral hyperopic defocus alters central refractive development in infant monkeys - Smith, Earl L. (2009)
Understanding the role of peripheral defocus on central refractive development is critical because refractive errors can vary significantly with eccentricity and peripheral refractions have been implicated in the genesis of central refractive errors in humans. Two rearing strategies were used to determine whether peripheral hyperopia alters central refractive development in rhesus monkeys. In intact eyes, lens-induced relative peripheral hyperopia produced central axial myopia. Moreover, eliminating the fovea by laser photoablation did not prevent compensating myopic changes in response to optically imposed hyperopia. These results show that peripheral refractive errors can have a substantial impact on central refractive development in primates.